(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2007)
The results of empirical studies on Kuznets environmental curves are discussed in the article as well as economic implications of findings of these studies. The relationship of economic growth and environmental impact has spurred fierce debates between growth optimists referring to the phenomenon of the environmental Kuznets curve, and pessimists referring to the limits to growth. The article draws some hints from a critical assessment of the literature on the environmental Kuznets curve. In particular it is argued that the optimistic implications of this literature on the sustainability management are not granted. However, environmental Kuznets curves analysis allows clarification of a few basic conditions to achieve pollution reduction with economic growth. These conditions can be met by implementing a systematic and strict environmental policy strategy aimed at shifting Kuznets relations downward.